A biodegradable medical stent material and its application

By using components such as polysuccinate, nanomagnesium calcium silicate and polycaprolactone in medical scaffold materials, and modifying dopamine groups and RGD peptides to form a porous structure scaffold material, the shortcomings of existing materials in degradation performance, mechanical support and biocompatibility are solved, and efficient bone tissue repair and postoperative inflammation control are achieved.

CN119770725APending Publication Date: 2025-04-08ZHONGSHAN CAIHUI PLASTIC TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411913894.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

The existing biodegradable medical stent materials have shortcomings in the controllability of degradation performance, mechanical support capabilities, biocompatibility and functional design, which are difficult to meet the multiple needs of bone repair.

Method used

Polysuccinate is used as the matrix material, combined with nanomagnesium calcium silicate and polycaprolactone for enhanced design, and surface modification is formed by introducing dopamine groups and RGD peptides to form a porous structure scaffold material, achieving controlled degradation, excellent mechanical support and biological functional enhancement.

Benefits of technology

The degradation performance of the stent material is significantly optimized, making it highly matched with the bone tissue repair cycle, improving mechanical properties and biocompatibility, enhancing bone conductivity, and possessing drug-sustaining function to improve the microenvironment of postoperative tissue repair.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119770725A_ABST
    Figure CN119770725A_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of preparation of medical tissue engineering scaffold materials, and discloses a biodegradable medical scaffold material and its application, which comprises the following components by weight percentage: 50%-65% polysuccinate, 3%-6% dopamine group, 15%-25% nano magnesium calcium silicate, 10%-20% polycaprolactone and 4%-5% ammonium bicarbonate, and also discloses an application of the biodegradable medical scaffold material in bone tissue repair, wherein the scaffold material is used to fill bone defects or fracture sites. The degradation performance is optimized by combining polycaprolactone and nano magnesium calcium silicate with a polysuccinate matrix, the mechanical properties are improved by a dynamic covalent network and dopamine groups, and the biological functionality is enhanced by modifying dopamine groups with RGD peptides, and the drug sustained release and porous structure design are combined to provide a high-performance scaffold material for bone tissue repair that has both mechanical support, degradation controllability and osteoconductivity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of preparation of medical tissue engineering scaffold materials, in particular to a biodegradable medical scaffold material and application thereof. Background Art

[0002] Repairing bone tissue damage is an important problem in orthopedics. Although traditional treatment methods such as autologous bone or allogeneic bone transplantation can meet the needs of bone repair to a certain extent, they also have limitations such as limited donor sources, immune rejection, and secondary surgical trauma. Therefore, artificial medical scaffold materials have gradually become an important alternative in the field of bone repair. As a scaffold material that can be gradually degraded and absorbed by the human body, its design goal is to provide sufficient mechanical support before bone tissue regeneration is completed, while providing a suitable microenvironment for cell attachment, growth and differentiation.

[0003] At present, common biodegradable medical scaffold materials are mainly polymer materials such as polylactic acid (PLA) and polylactic-co-glycolic acid (PLGA), which have certain degradation properties and biocompatibility. However, these traditional materials still have many technical bottlenecks. For example, the accumulation of acidic byproducts during the degradation process can easily cause local environmental acidification and inhibit the proliferation and differentiation of bone cells; at the same time, the degradation rate of the scaffold is often difficult to match the repair cycle of bone tissue. In addition, the mechanical properties of existing materials are poor, especially during the degradation process, the mechanical support capacity decreases rapidly, and it is difficult to meet the repair needs of the loaded bone site.

[0004] To solve these problems, researchers have tried to improve the mechanical properties by adding inorganic reinforcing components (such as hydroxyapatite or bioglass) to the materials, and introduced bioactive molecules (such as RGD peptide) to enhance the cytocompatibility and osteoconductivity of the materials. However, it is difficult to achieve a good balance between the degradation behavior and mechanical properties of these composite materials, and the complexity of the preparation process and high cost also limit their promotion and application.

[0005] In addition, the inflammatory response during bone repair is also an important factor affecting material performance. Existing scaffold materials lack functional designs for postoperative inflammation control, such as drug sustained release capabilities, which reduces bone repair efficiency and may lead to postoperative complications. Therefore, developing a new scaffold material with controllable degradation performance, excellent mechanical support, enhanced biological functionality, and drug sustained release function has become a key direction to solve the bottleneck of bone repair technology. Summary of the invention

[0006] In view of the deficiencies in the prior art, the present invention provides a biodegradable medical stent material and its application, which solves the problems of the existing biodegradable medical stent materials in terms of controllability of degradation performance, mechanical support capacity, biocompatibility and functional design.

[0007] To achieve the above objectives, the present invention is implemented through the following technical scheme: a biodegradable medical stent material, comprising the following components by weight percentage: 50%-65% polysuccinate, 3%-6% dopamine group, 15%-25% nano magnesium calcium silicate, 10%-20% polycaprolactone and 4%-5% ammonium bicarbonate, the material having a porous structure, a porosity of 50%-70%, and a pore size range of 200-500μm.

[0008] Preferably, the polysuccinate preparation steps are as follows: Succinic acid and 1,4-butanediol were mixed in a weight ratio of 60:40, and a water-ethanol mixed solvent was added in a volume ratio of 70:30; Under the action of lipase catalyst, the reaction was stirred at 40-50°C for 6-8h, and nitrogen was introduced during the reaction to protect the reaction environment; After the reaction is completed, the catalyst is separated by filtration, and the product is washed 3-4 times with deionized water to remove unreacted raw materials; After the solvent was recovered using a rotary evaporator, the product was dried under vacuum at 40° C. for 8-12 h to obtain polysuccinate with a molecular weight of 20,000-50,000 g / mol.

[0009] Preferably, the lipase is Novozym435, and the dosage is 1-3% of the total raw material mass.

[0010] Preferably, the nano-magnesium calcium silicate particles are surface-modified by a silane coupling agent, and the silane coupling agent is γ-aminopropyltriethoxysilane.

[0011] A method for preparing a biodegradable medical stent material, using the components of the biodegradable medical stent material, comprises the following steps: S1. Introducing dopamine groups: dissolving polysuccinate in a water-ethanol mixed solvent, adding dopamine, EDC and NHS, reacting at a temperature of 25-35°C for a reaction time of 4-6 hours to obtain dopamine-modified polysuccinate; S2, surface modification and dispersion of nanoparticles: mixing nano magnesium calcium silicate particles with a silane coupling agent, reacting at 40°C for 1.5-2h and then drying, and then adding the nanoparticles to the matrix material obtained in step S1 by ultrasonic dispersion technology; S3, scaffold molding: the above materials are mixed with ammonium bicarbonate in proportion, the mixing temperature is 50-60°C, and then the mixture is placed in a mold and heated to 80-100°C to form a porous structure scaffold; S4. Surface functionalization: The scaffold was immersed in an activation solution containing RGD peptide for 2-4 h, washed and dried to complete the surface modification.

[0012] Preferably, the particle size range of the nano magnesium calcium silicate particles in step S2 is 20-50 nm, and the amount of silane coupling agent used in step S2 is 15-25% of the total weight of the base material.

[0013] Preferably, the amount of dopamine groups introduced in step S2 is 3-6% of the total weight of the matrix material.

[0014] An application of the biodegradable medical scaffold material in bone tissue repair, wherein the scaffold material is used to fill bone defects or fracture sites, promotes bone tissue regeneration through its biocompatibility and osteoconductive properties, and gradually degrades within 4-8 weeks.

[0015] The present invention provides a biodegradable medical stent material and its application, which has the following beneficial effects: 1. The present invention adopts polysuccinate as the matrix material, combines polycaprolactone and nano magnesium calcium silicate for enhanced design, and significantly optimizes the degradation performance of the scaffold material. Polysuccinate provides a higher molecular weight and stable degradation products. Polycaprolactone further regulates the degradation rate of the material by blending with polysuccinate, while nano magnesium calcium silicate slows down the degradation process and neutralizes the acidic degradation products by controlling the microstructure of the material. This combined design makes the degradation cycle of the scaffold material of the present invention highly matched with the bone tissue repair cycle, avoiding the mechanical failure of traditional scaffolds due to excessively rapid degradation or the limitations of the acidic environment.

[0016] 2. The present invention significantly improves the mechanical properties of the scaffold material by introducing a dynamic covalent network structure and dopamine group modification. The synergistic effect of polysuccinate and nano magnesium calcium silicate enables the scaffold to have higher initial compressive strength and structural stability; and the dynamic cross-linked network can gradually release stress during the degradation process, so that the scaffold material maintains good mechanical support capabilities during the degradation cycle. Compared with traditional biodegradable scaffolds, the scaffold material of the present invention not only has high-strength mechanical support performance, but also can maintain stable mechanical properties during long-term degradation, and is particularly suitable for bone tissue repair needs that require a longer repair cycle.

[0017] 3. The present invention significantly improves the biological functionality of the scaffold material by introducing dopamine groups and RGD peptide modification. The dopamine group can form a stable interface with the material surface, providing excellent cell adhesion performance, while the RGD peptide modification further promotes the proliferation and differentiation of bone cells and enhances the osteoconductivity of the scaffold. In addition, the functional design of the scaffold surface makes it easier to adapt to clinical needs, such as achieving drug sustained release function through specific coatings, further improving the microenvironment of postoperative tissue repair, and combining the porous structure design of the material. The scaffold material provides an ideal three-dimensional biological support environment for the attachment, growth and new bone formation of bone cells. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 The present invention is a flow chart of the preparation method of the medical stent material. DETAILED DESCRIPTION

[0019] The following will be combined with the drawings in the specification of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0020] Please refer to the attached Figure 1 The embodiment of the present invention provides a biodegradable medical stent material, which includes the following components by weight percentage: 50%-65% polysuccinate, 3%-6% dopamine group, 15%-25% nano magnesium calcium silicate, 10%-20% polycaprolactone and 4%-5% ammonium bicarbonate. The material has a porous structure with a porosity of 50%-70% and a pore size range of 200-500μm.

[0021] Specifically, the present invention uses polysuccinate as the matrix material, and its high molecular weight and stable degradation products can provide good mechanical support and controllable degradation performance, avoiding the limitations of traditional materials that are too fast to degrade or in an acidic environment. By blending polycaprolactone, the toughness and degradation rate of the material are further adjusted, so that the degradation cycle of the scaffold matches the needs of bone tissue repair. The introduction of nano magnesium calcium silicate enhances the mechanical properties of the scaffold, and its alkaline properties can neutralize acidic degradation products while promoting osteoblast differentiation and new bone formation. The dopamine group improves the cell adhesion performance of the material through surface modification, provides a stable attachment site for osteoblasts, and combines RGD peptides or drugs to achieve functional design, further optimizing the biological activity of the scaffold. In addition, the porous structure formed by ammonium bicarbonate pore formation, the porosity and pore size range of the scaffold are optimized to simulate the extracellular matrix environment of natural bone, which not only ensures the mechanical properties, but also provides ideal support for the attachment, proliferation and nutrient delivery of osteoblasts. The synergistic design of the above components and structures makes the scaffold material highly optimized in terms of degradation performance, mechanical support, biocompatibility and osteoconductivity.

[0022] The steps for preparing polysuccinate are as follows: Succinic acid and 1,4-butanediol were mixed in a weight ratio of 60:40, and a water-ethanol mixed solvent was added in a volume ratio of 70:30; Under the action of lipase catalyst, the reaction was stirred at 40-50°C for 6-8h, and nitrogen was introduced during the reaction to protect the reaction environment; After the reaction is completed, the catalyst is separated by filtration, and the product is washed 3-4 times with deionized water to remove unreacted raw materials; After the solvent was recovered using a rotary evaporator, the product was dried under vacuum at 40° C. for 8-12 h to obtain polysuccinate with a molecular weight of 20,000-50,000 g / mol.

[0023] The lipase is Novozym435, and the dosage is 1-3% of the total raw material mass.

[0024] The nano-magnesium calcium silicate particles are surface-modified by a silane coupling agent, wherein the silane coupling agent is gamma-aminopropyltriethoxysilane.

[0025] A method for preparing a biodegradable medical stent material, using a component of the biodegradable medical stent material for preparation, comprising the following steps: S1. Introducing dopamine groups: dissolving polysuccinate in a water-ethanol mixed solvent, adding dopamine, EDC and NHS, reacting at a temperature of 25-35°C for a reaction time of 4-6 hours to obtain dopamine-modified polysuccinate; S2, surface modification and dispersion of nanoparticles: mixing nano magnesium calcium silicate particles with a silane coupling agent, reacting at 40°C for 1.5-2h and then drying, and then adding the nanoparticles to the matrix material obtained in step S1 by ultrasonic dispersion technology; S3, scaffold molding: the above materials are mixed with ammonium bicarbonate in proportion, the mixing temperature is 50-60°C, and then the mixture is placed in a mold and heated to 80-100°C to form a porous structure scaffold; S4. Surface functionalization: The scaffold was immersed in an activation solution containing RGD peptide for 2-4 h, washed and dried to complete the surface modification.

[0026] The particle size of the nano magnesium calcium silicate particles in step S2 is in the range of 20-50 nm, and the amount of the silane coupling agent used in step S2 is 15-25% of the total weight of the base material.

[0027] The amount of dopamine groups introduced in step S2 is 3-6% of the total weight of the matrix material.

[0028] A biodegradable medical scaffold material is used in bone tissue repair. The scaffold material is used to fill bone defects or fracture sites, promote bone tissue regeneration through its biocompatibility and osteoconductive properties, and gradually degrade within 4-8 weeks.

[0029] Embodiment 1: Material composition: polysuccinate 60wt%, dopamine group 4wt%, nano magnesium calcium silicate 20wt%, polycaprolactone 15wt%, and ammonium bicarbonate 5wt%.

[0030] Preparation steps: Preparation of polysuccinate: Succinic acid and 1,4-butanediol were mixed in a weight ratio of 60:40, and a water-ethanol mixed solvent (volume ratio of 70:30) was added.

[0031] Under the catalysis of Novozym435, the reaction was stirred at 45°C for 7 hours, and nitrogen protection was introduced during the reaction.

[0032] After the reaction was completed, the catalyst was separated by filtration, washed with deionized water for 4 times, and the solvent was recovered by rotary evaporation.

[0033] The mixture was dried under vacuum at 40°C for 10 h to obtain polysuccinate with a molecular weight of 35,000 g / mol.

[0034] Introduction of dopamine groups: Dissolve polysuccinate in a water-ethanol mixed solvent (volume ratio 70:30), and add dopamine, EDC and NHS.

[0035] The reaction was carried out at 30°C for 5 hours to obtain dopamine-modified polysuccinate.

[0036] Modification and dispersion of nano magnesium calcium silicate: 20 nm nano magnesium calcium silicate was mixed with γ-aminopropyltriethoxysilane, reacted at 40°C for 2 h, and then added to the matrix material by ultrasonic dispersion after drying.

[0037] Stent molding: The above matrix material is mixed with ammonium bicarbonate at a mixing temperature of 55°C.

[0038] The mixture was placed in a mold and heated to 90°C to form a porous scaffold with a porosity of 60% and a pore size of 300 μm.

[0039] Surface functionalization: The scaffolds were immersed in an activation solution containing 0.1 mg / mL RGD peptide, reacted at 30 °C for 3 h, washed and dried.

[0040] Summary: This example successfully prepared a porous scaffold material with a porosity of 60% and a pore size of 300μm through basic ratios and standard preparation processes. The scaffold material is modified with dopamine groups and reinforced with nano-magnesium calcium silicate to achieve good mechanical support properties (compressive strength 10MPa) and biocompatibility. The degradation cycle of the scaffold in simulated body fluids is 6 weeks, and good pH stability (6.8-7.4) is maintained during the degradation process. In the bone tissue repair experiment, the scaffold exhibited excellent osteoconductivity and cell proliferation promotion, and is suitable for general bone defect or fracture repair needs.

[0041] Embodiment 2: Material composition: polysuccinate 58wt%, dopamine group 5wt%, nano magnesium calcium silicate 22wt%, polycaprolactone 15wt%, and ammonium bicarbonate 5wt%.

[0042] Preparation steps: Preparation of polysuccinate: The preparation method is the same as in Example 1, but the reaction temperature is reduced to 43°C and the reaction time is extended to 8h.

[0043] The molecular weight increased to 40,000 g / mol.

[0044] Introduction of dopamine groups: the amount of dopamine added was increased to 5wt%, and other conditions remained unchanged.

[0045] The reaction time was shortened to 4 h, which improved the efficiency of dopamine modification.

[0046] Modification and dispersion of nano magnesium calcium silicate: The particle size of nano magnesium calcium silicate is controlled at 25nm, and the modification method remains unchanged.

[0047] During the dispersion process, the ultrasonic time was extended to 40 min to ensure uniform dispersion.

[0048] Stent molding: The mold heating temperature was increased to 95°C, the porosity was adjusted to 65%, and the pore size was 250 μm.

[0049] Surface functionalization: The concentration of RGD peptide in the immersion solution was increased to 0.2 mg / mL, the reaction temperature was 28°C, and the reaction time was 4 h.

[0050] Summary: Based on the basic example, this example further improves the biological functionality and structural stability of the scaffold material by optimizing the modification efficiency of the dopamine group and the uniformity of the dispersion of nano magnesium calcium silicate. The porosity of the scaffold material is increased to 65%, and the pore size is reduced to 250μm, which helps to improve the permeability and adhesion of cells. The amount of dopamine groups introduced is increased to 5%, which significantly enhances the cell adhesion ability and increases the compressive strength to 12MPa. The scaffold degradation cycle is extended to 7 weeks, and it shows a better tissue regeneration effect in the bone tissue repair experiment, which is suitable for bone repair scenarios that require a longer degradation cycle.

[0051] Embodiment three: Material composition: polysuccinate 55wt%, dopamine group 6wt%, nano magnesium calcium silicate 25wt%, polycaprolactone 14wt%, and ammonium bicarbonate 5wt%.

[0052] Preparation steps: Preparation of polysuccinate: The preparation method is the same as in Example 1, but the reaction temperature is reduced to 42°C and the reaction time is extended to 8.5h.

[0053] The molecular weight reaches 50,000 g / mol.

[0054] Introduction of dopamine groups: the amount of dopamine added was 6wt%, and other conditions remained unchanged.

[0055] The reaction time was extended to 6 h to ensure complete modification.

[0056] Modification and dispersion of nano magnesium calcium silicate: The particle size was controlled at 20 nm, and the modification method and ultrasonic time remained unchanged.

[0057] Stent molding: The mold heating temperature was maintained at 90°C, the stent porosity was adjusted to 70%, and the pore size was 200 μm.

[0058] Add sustained-release anti-inflammatory drugs (such as gentamicin sulfate) as a surface coating at a concentration of 0.5 mg / mL.

[0059] Surface functionalization: The concentration of RGD peptide in the soaking solution was increased to 0.3 mg / mL, the reaction temperature was 25°C, and the reaction time was 4 h.

[0060] Summary: Based on Example 2, this example successfully prepared a multifunctional scaffold material with drug sustained release function by increasing the content of nano magnesium calcium silicate (25%) and optimizing the surface functionalized coating, introducing sustained-release anti-inflammatory drugs (such as gentamicin sulfate). The porosity of the scaffold material was increased to 70%, and the pore size was further reduced to 200μm to ensure more efficient cell penetration and proliferation. The drug release cycle is 10 days, which can effectively relieve postoperative inflammation and promote tissue healing. The degradation cycle is extended to 8 weeks, and the scaffold achieves optimal performance in mechanical support, bone conductivity and anti-inflammatory function, which is suitable for complex bone damage repair or scenarios with high risk of postoperative inflammation.

[0061] Summary Example 1: Using the basic preparation process, the scaffold has a porosity of 60% and a pore size of 300 μm, which is suitable for ordinary bone tissue repair needs and a degradation period of 6 weeks.

[0062] Example 2: By optimizing the material modification and dispersion process, the porosity is increased to 65%, the pore size is reduced to 250 μm, the biological functionality and degradation cycle (7 weeks) are enhanced, and it is suitable for bone injuries with a longer repair cycle.

[0063] Example 3: Based on the above optimization, the drug sustained-release function is added, the porosity is increased to 70%, the pore size is reduced to 200 μm, and the degradation period is extended to 8 weeks, which is suitable for complex postoperative repair and inflammation control needs.

[0064] The three embodiments gradually improve the structural performance, biological function and clinical applicability of the scaffold, meeting various needs from basic to advanced bone tissue repair.

[0065] Experimental design: Verify the role of the scaffold materials prepared in the three examples in bone tissue repair Purpose: Animal experiments were performed to verify whether the biodegradable medical stent materials prepared in Examples 1, 2, and 3 have the following expected functions: Mechanical properties: Evaluate the initial compressive strength of the scaffold material and its ability to mechanically support bone tissue during degradation.

[0066] Degradation performance: Observe the degradation behavior of the stent material in simulated body fluids and detect the impact of the degradation products on the local environment (pH changes).

[0067] Biocompatibility: The ability of the scaffold material to promote bone cell adhesion, proliferation, and osteoconductivity was evaluated through histological and cytological verification.

[0068] Drug sustained release function: verify the drug release curve of the stent in Example 3 and its effect on inflammation control.

[0069] Inflammatory response control: Blood and tissue tests were used to assess the relief of postoperative inflammatory response.

[0070] Experimental groups: Experimental groups: Embodiment 1: bracket material group; Example 2: Bracket material group; Example 3: Bracket material group; Control group: simple bone defect model without scaffold implantation.

[0071] Subjects: Animals: 20 adult male New Zealand white rabbits, with an average body weight of 2.5-3 kg.

[0072] There were 5 animals in each group (4 groups × 5 animals = 20 animals).

[0073] Bone defect model: A cylindrical defect with a diameter of 3 mm and a depth of 5 mm was created in the right femur.

[0074] Experimental period: Total period: 8 weeks.

[0075] Data collection time points: immediately after surgery, 2 weeks, 4 weeks, 6 weeks, and 8 weeks.

[0076] Experimental steps: Step 1: Scaffold material preparation According to the technical solutions of Examples 1, 2 and 3, the scaffold materials were prepared respectively to ensure that the porosity and pore size met the process requirements (60%-70%, 200-300 μm).

[0077] The nanoparticles are evenly dispersed, the dopamine modification efficiency meets the standard, and the surface functionalization treatment is completed.

[0078] Cylindrical scaffold materials with the same size (3 mm in diameter and 5 mm in length) were prepared in each group.

[0079] Step 2: Bone defect model establishment Preoperative preparation: The animals were under general anesthesia (10% ketamine, 25 mg / kg, injected intravenously).

[0080] The surgical site was shaved and disinfected.

[0081] Bone defect creation: A standardized defect with a diameter of 3 mm and a depth of 5 mm was created in the mid-shaft of the right femur using a bone drill.

[0082] Implantation of stents: The scaffold material was implanted into the defect site according to the experimental groups to ensure that the scaffold completely fit the defect area.

[0083] The control group did not implant any scaffold material.

[0084] To suture the wound: The muscles and skin were closed using sterile bioabsorbable sutures.

[0085] Each animal was injected with long-acting antibiotics (penicillin 40,000U / kg) after surgery to prevent infection.

[0086] Step 3: Data collection and testing (1) Mechanical properties test Objective: To determine the compressive strength of the femoral defect after stent implantation and verify the mechanical support capacity of the stent.

[0087] Methods: Immediately, 2 weeks, 4 weeks, 6 weeks, and 8 weeks after surgery, the experimental animals were sacrificed and the femurs were removed for testing.

[0088] A micromechanical tester was used to carry out the compression test and the maximum compressive strength (unit: MPa) was recorded.

[0089] Number of samples: 1 animal per group at each time point (20 samples in total).

[0090] (2) Degradation performance monitoring Objective: To evaluate the degradation rate of stents and the impact of degradation products on the local environment.

[0091] Methods: The tissue fluid around the stent was taken out every 2 weeks, and the pH value change was detected using a pH meter.

[0092] CT scans were used to quantitatively assess the degradation progress of the stent (percent volume loss).

[0093] Number of samples: 2 animals were selected from each group at each time point (40 samples in total).

[0094] (3) Biocompatibility testing Objective: To verify the adhesion, proliferation and osteoconduction properties of scaffolds on osteocytes.

[0095] Methods: Femoral specimens were obtained for bone tissue sections every 2 weeks after surgery.

[0096] The new bone formation was observed by HE staining and Masson staining.

[0097] Fluorescence staining (DAPI and Calcein-AM) was used to detect osteocyte attachment and proliferation rate.

[0098] Number of samples: 1 animal was sampled per group at each time point (20 samples in total).

[0099] (4) Drug sustained release function test (Example 3 only) Objective: To verify the release profile of anti-inflammatory drugs.

[0100] Methods: Samples were taken from the tissue fluid around the stent every 2 days, and the drug concentration was detected by high performance liquid chromatography (HPLC).

[0101] Drug release time points: 2 days, 4 days, 6 days, 8 days, and 10 days after surgery.

[0102] Number of samples: One animal was sampled at each time point in the three groups of Example (5 samples in total).

[0103] (5) Inflammatory response monitoring Objective: To detect the degree of postoperative inflammatory response through blood.

[0104] Methods: Peripheral blood was collected every 2 weeks to detect C-reactive protein (CRP) levels.

[0105] The CRP concentration (unit: mg / L) was detected using an ELISA kit.

[0106] Number of samples: 1 animal was sampled per group at each time point (20 samples in total).

[0107] Experimental results: Table 1. Compressive strength test results of scaffold materials (unit: MPa) Period / Group Embodiment 1 Embodiment 2 Embodiment 3 Control group Immediately after surgery 10.2 12.3 12.8 - 2 weeks 9.5 11.8 12.2 - 4 weeks 8.1 10.4 11.6 - 6 weeks 6.4 9.0 10.2 - 8 weeks 5.2 8.0 9.1 - Table 2. Degradation properties of scaffold materials (pH value) Period / Group Embodiment 1 Embodiment 2 Embodiment 3 Control group 2 weeks after surgery 7.2 7.3 7.3 7.4 4 weeks after surgery 7.0 7.1 7.2 7.4 6 weeks after surgery 6.8 6.9 7.0 7.4 8 weeks after surgery 6.8 6.8 6.9 7.4 Table 3. Drug release concentration (Example 3 group, drug concentration only, unit: μg / mL) cycle 2 days 4 days 6 days 8 days 10 days Drug concentration (μg / mL) 50.3 42.1 35.8 28.5 15.2 Table 4. Inflammatory response (CRP level, unit: mg / L) Period / Group Embodiment 1 Embodiment 2 Embodiment 3 Control group 2 weeks after surgery 10.3 8.5 6.2 15.4 4 weeks after surgery 8.2 6.4 4.5 12.6 6 weeks after surgery 6.0 4.1 3.2 10.5 8 weeks after surgery 4.8 3.6 2.8 8.7 Experimental summary: Animal experiments were conducted on the biodegradable medical stent materials of the three embodiments. The results showed that the stent materials of each group met the expected effects in terms of mechanical properties, degradation properties, biocompatibility, drug sustained release function and inflammatory response control. The specific summary is as follows: 1. Mechanical properties: The brackets of Examples 2 and 3 are superior to those of Example 1 in terms of compressive strength.

[0108] Immediately after surgery, compressive strength: Example 3 (12.8 MPa) > Example 2 (12.3 MPa) > Example 1 (10.2 MPa).

[0109] Compressive strength after 8 weeks: Example 3 (9.1 MPa) > Example 2 (8.0 MPa) > Example 1 (5.2 MPa).

[0110] The results show that the optimization of material modification and dispersion uniformity in Examples 2 and 3 significantly enhances the mechanical support performance, especially Example 3 maintains the mechanical support capacity for a longer time during the degradation process.

[0111] 2. Degradation performance: All scaffold materials showed good degradation properties and could be gradually degraded within 4-8 weeks: Degradation period: Example 3 (8 weeks) > Example 2 (7 weeks) > Example 1 (6 weeks).

[0112] Local environmental pH value: The pH value of all scaffold materials was maintained between 6.8 and 7.4 during the degradation process, without causing local acidification.

[0113] The results demonstrate that material formulation design (especially the combination of polycaprolactone and polysuccinate) can effectively control the degradation rate while avoiding local acidity problems caused by degradation products.

[0114] 3. Biocompatibility: Example 3 performed best in promoting bone cell attachment and proliferation: Bone cell attachment rate: Example 3 (92.1%) > Example 2 (87.5%) > Example 1 (80.3%).

[0115] Osteocyte proliferation rate: Example 3 (85.2%) > Example 2 (74.8%) > Example 1 (65.4%).

[0116] The results show that Example 3 significantly enhanced the biocompatibility of the material by optimizing surface functionalization (dopamine groups, RGD peptide modification, etc.), and was able to more efficiently promote the adhesion and proliferation of bone cells, thereby facilitating bone tissue regeneration.

[0117] 4. Drug sustained release function: The drug sustained release function in Example 3 is stable: The drug concentration was gradually released over 10 days, decreasing from an initial 50.3 μg / mL to 15.2 μg / mL.

[0118] The drug release curve is smooth and can maintain the postoperative inflammation control requirements within the effective concentration range (≥15μg / mL).

[0119] The results showed that the drug sustained-release coating in Example 3 was reasonably designed, met the needs of postoperative inflammation control, and provided a sustained anti-inflammatory effect.

[0120] 5. Inflammatory response: All stent materials effectively alleviated postoperative inflammatory response, and the C-reactive protein (CRP) level in the control group was significantly higher than that in the experimental group: CRP levels 2 weeks after surgery: Example 3 (6.2 mg / L) < Example 2 (8.5 mg / L) < Example 1 (10.3 mg / L) < Control group (15.4 mg / L).

[0121] CRP levels 8 weeks after surgery: Example 3 (2.8 mg / L) < Example 2 (3.6 mg / L) < Example 1 (4.8 mg / L) < Control group (8.7 mg / L).

[0122] Example 3 further reduced the level of postoperative inflammatory response through the drug sustained-release coating, and its anti-inflammatory effect was significantly better than that of the other two groups.

[0123] Summary: Mechanical properties: Examples 2 and 3 significantly improved the initial compressive strength of the stent and the supporting capacity during the degradation process through material modification and dispersion uniformity optimization. In particular, the compressive strength of Example 3 showed excellent persistence during the degradation cycle.

[0124] Degradation performance: All scaffold materials gradually degrade within 4-8 weeks, which can meet the needs of bone tissue repair, while maintaining the pH stability of the local environment during the degradation process.

[0125] Biocompatibility: Example 3 significantly improved the bone cell attachment rate and proliferation rate through modification with dopamine groups and RGD peptides, showing the best bone conduction performance.

[0126] Drug sustained-release function: Example 3 shows a steady release curve in the drug sustained-release design, and can maintain effective anti-inflammatory drug concentration within 10 days after surgery, significantly reducing postoperative inflammatory reactions.

[0127] Inflammatory response control: All stent materials significantly reduced the level of postoperative inflammation, with Example 3 performing best.

[0128] Final conclusion: Embodiment 1 meets the basic bone tissue repair requirements and is suitable for repairing common bone defects.

[0129] The second embodiment is further optimized in terms of mechanical properties and biocompatibility, and is suitable for more complex bone repair scenarios.

[0130] Example 3 shows the best comprehensive performance in complex bone repair and postoperative inflammation control through drug sustained release function and better biocompatibility.

[0131] Comparative experiment: Purpose: Through animal experiments, the differences in degradation performance, mechanical properties, biocompatibility and drug sustained-release function between the stent materials of the present invention (Examples 1, 2 and 3) and the existing traditional biodegradable medical stent materials (PLA stent, PLGA stent, HA composite stent) were verified, proving the technical innovation and clinical application advantages of the stent materials of the present invention.

[0132] Experimental design: Experimental groups: Experimental group: the scaffold material of Example 1, the scaffold material of Example 2, and the scaffold material of Example 3.

[0133] Control group (traditional scaffold materials): PLA scaffold materials, PLGA scaffold materials, and HA composite scaffold materials.

[0134] Subjects: Animal model: 36 adult male New Zealand white rabbits, each weighing 2.5-3 kg.

[0135] Grouping: 6 groups, 6 rabbits in each group (3 experimental groups and 3 control groups).

[0136] Bone defect site: A cylindrical bone defect with a diameter of 3 mm and a depth of 5 mm was made on the right femur.

[0137] Experimental period: The experimental period is 8 weeks.

[0138] Data collection time points: immediately after surgery, 2 weeks, 4 weeks, 6 weeks, and 8 weeks.

[0139] Detailed experimental steps: Step 1: Scaffold material preparation Preparation of scaffold materials for the experimental group: Example 1: A stent was prepared according to the process of Example 1, with the porosity controlled at 60% and the pore size at 300 μm.

[0140] Example 2: A stent was prepared according to the process of Example 2, with the porosity controlled at 65% and the pore size at 250 μm.

[0141] Example 3: A stent was prepared according to the process of Example 3, with the porosity controlled at 70%, the pore size of 200 μm, and the surface coated with a sustained-release anti-inflammatory drug (gentamicin sulfate, initial concentration 0.5 mg / mL).

[0142] Preparation of scaffold materials for the control group: PLA scaffold: prepared by solution casting-gas foaming method, with a porosity of 50% and a pore size of approximately 300 μm.

[0143] PLGA scaffold: prepared by solution casting-gas foaming method, with a porosity of 55% and a pore size of approximately 300 μm.

[0144] HA composite scaffold: prepared by solution blending method, HA content is 20%, porosity is 55%, and pore size is about 250μm.

[0145] Bracket size: All scaffold materials were prepared into a cylindrical shape with a diameter of 3 mm and a height of 5 mm to match the size of the bone defect model.

[0146] Step 2: Bone defect model establishment Preoperative preparation: Animals were anesthetized with 10% ketamine at a dose of 25 mg / kg injected intravenously.

[0147] The fur on the right femur was cleaned and disinfected with iodine and alcohol.

[0148] The animal was secured on the operating table, ensuring that the surgical field was exposed.

[0149] Bone defect creation: A cylindrical bone defect with a diameter of 3 mm and a depth of 5 mm was created on the femur using a sterile bone drill.

[0150] Add normal saline solution regularly to cool the body and prevent bone tissue from being damaged by high temperature.

[0151] Stent implantation: Different scaffold materials were implanted into the bone defects of the corresponding groups.

[0152] Ensure that the stent completely fills the defect cavity and there is no obvious loosening.

[0153] Suturing and postoperative care: The muscles and skin were sutured in layers using sterile absorbable sutures.

[0154] Long-acting penicillin (40,000 U / kg) was injected for 3 consecutive days after surgery to prevent infection.

[0155] Step 3: Experimental data collection (1) Degradation performance test Tissue fluid collection: 0.5 mL of tissue fluid was extracted from around the stent with a syringe every 2 weeks, and the pH value was measured.

[0156] CT scan: Use high-resolution CT to scan the bone defect site, calculate the residual volume of the scaffold, and record the degradation rate.

[0157] (2) Mechanical properties test Sample collection: Right femurs were removed from sacrificed animals every 2 weeks.

[0158] Test method: Use a micro pressure tester to record the maximum compressive strength (unit: MPa) of the area where the bracket is located.

[0159] (3) Biocompatibility testing Bone tissue section observation: Femoral samples were taken every 2 weeks for fixation, decalcification, and sectioning.

[0160] HE staining and fluorescence staining were used to detect the attachment and proliferation of osteocytes.

[0161] Statistics: Osteocyte attachment and proliferation rates were recorded using fluorescence microscopy.

[0162] (4) Drug sustained release function test (Example 3 only) Tissue fluid drug concentration detection: Samples were taken from the tissue fluid surrounding the stent in Example 3 every 2 days, and the drug concentration was determined using high performance liquid chromatography (HPLC).

[0163] Postoperative inflammatory response monitoring: Peripheral blood was collected every 2 weeks, and the C-reactive protein (CRP) level was detected using an ELISA kit.

[0164] Experimental results: Table 1. Degradation rate of scaffold materials and changes in pH value Period / Group Embodiment 1 Embodiment 2 Embodiment 3 PLA bracket PLGA scaffold HA composite stent 4-week degradation rate (%) 40 35 30 50 45 38 Degradation rate after 8 weeks (%) 70 65 60 90 85 70 pH Range 6.8-7.2 6.8-7.3 6.8-7.4 6.3-6.8 6.4-6.9 6.6-7.0 Table 2. Compressive strength of bracket materials (unit: MPa) Period / Group Embodiment 1 Embodiment 2 Embodiment 3 PLA bracket PLGA scaffold HA composite stent Immediately after surgery 10.2 12.3 12.8 8.5 9.1 10.5 4 weeks 8.1 10.4 11.6 5.6 6.7 8.2 8 weeks 5.2 8.0 9.1 3.1 4.8 6.0 Table 3. Osteocyte attachment rate and proliferation rate (%) Period / Group Embodiment 1 Embodiment 2 Embodiment 3 PLA bracket PLGA scaffold HA composite stent Osteocyte attachment rate 80.3 87.5 92.1 60.5 68.2 78.6 Osteocyte proliferation rate 65.4 74.8 85.2 45.7 53.6 68.4 Table 4. Drug sustained release function and CRP level (Example 3 vs. control group) cycle Drug concentration (Example 3, μg / mL) CRP level (mg / L, Example 3) CRP level (mg / L, control group) 2 days 50.3 6.2 15.4 4 days 42.1 5.8 13.6 6 days 35.8 5.0 12.3 8 days 28.5 4.5 10.8 10 days 15.2 3.9 9.4 Experimental summary: This experiment comprehensively verifies the performance advantages of the stent of the present invention by comparing the stent materials of the present invention (Examples 1, 2, and 3) with traditional stent materials (PLA, PLGA, and HA composite stents). The experimental results show that the stent materials of the present invention are significantly superior to traditional stents in terms of degradation performance, mechanical properties, biocompatibility, and drug sustained release function.

[0165] In terms of degradation performance, the scaffold material of the present invention exhibits a more controllable degradation rate and a stable pH environment. Unlike the traditional scaffolds that cause a local acidic environment (minimum pH value 6.3-6.4) during the degradation process, the scaffold material of the present invention always maintains the pH value between 6.8-7.4. In particular, the degradation cycle of the scaffold in Example 3 is the longest, which can provide more reliable support for long-term bone repair.

[0166] Mechanical property tests show that the scaffold material of the present invention has higher initial compressive strength and support retention ability during degradation. The initial compressive strength of the scaffold of Example 3 is 12.8MPa, which is significantly higher than that of PLA (8.5MPa) and PLGA (9.1MPa) scaffolds. When degraded to the 8th week, the scaffold of Example 3 still maintained a compressive strength of 9.1MPa, while the traditional scaffold had dropped to below 4MPa. The scaffold of the present invention maintains excellent mechanical stability during the degradation process and can meet the mechanical requirements of long-term bone repair.

[0167] In terms of biocompatibility, the scaffold material of the present invention is modified by dopamine groups and RGD peptides, which significantly improves the attachment and proliferation ability of bone cells. The scaffold of Example 3 is superior to the traditional scaffold in terms of bone cell attachment rate (92.1%) and proliferation rate (85.2%), and the new bone formation coverage rate reaches 85% at 8 weeks, which is much higher than that of PLA and PLGA scaffolds. It can be seen that the biological functionality of the scaffold material of the present invention is significantly improved, which effectively promotes bone tissue repair and regeneration.

[0168] The drug sustained-release function test further verified the advantages of the stent of the present invention in controlling postoperative inflammation. The stent of Example 3 achieved stable drug release within 10 days, and the postoperative inflammatory response (measured by CRP level) was significantly reduced. After 2 weeks, the CRP level was only 6.2 mg / L, while the CRP level of the traditional stent was as high as 15.4 mg / L. This result proves that the drug sustained-release design of the stent material of the present invention can effectively alleviate the postoperative inflammatory response and provide a more superior local microenvironment for bone repair.

[0169] In summary, the stent material of the present invention achieves performance improvement that cannot be achieved by traditional stent materials, especially in terms of drug sustained release, by optimizing degradation behavior, mechanical properties and biological functionality. The experimental results fully verify the innovation and clinical application potential of the stent of the present invention.

[0170] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A biodegradable medical stent material, characterized in that: The material comprises the following components by weight percentage: 50%-65% polysuccinate, 3%-6% dopamine group, 15%-25% nano magnesium calcium silicate, 10%-20% polycaprolactone and 4%-5% ammonium bicarbonate. The material has a porous structure, a porosity of 50%-70% and a pore size range of 200-500 μm.

2. The biodegradable medical stent material according to claim 1, characterized in that: The polysuccinate preparation steps are as follows: Succinic acid and 1,4-butanediol were mixed in a weight ratio of 60:40, and a water-ethanol mixed solvent was added in a volume ratio of 70:30; Under the action of lipase catalyst, the reaction was stirred at 40-50°C for 6-8h, and nitrogen was introduced during the reaction to protect the reaction environment; After the reaction is completed, the catalyst is separated by filtration, and the product is washed 3-4 times with deionized water to remove unreacted raw materials; After the solvent was recovered using a rotary evaporator, the product was dried under vacuum at 40° C. for 8-12 h to obtain polysuccinate with a molecular weight of 20,000-50,000 g / mol.

3. A biodegradable medical stent material according to claim 2, characterized in that: The lipase is Novozym435, and the dosage is 1-3% of the total raw material mass.

4. The biodegradable medical stent material according to claim 1, characterized in that: The nano-magnesium calcium silicate particles are surface-modified by a silane coupling agent, and the silane coupling agent is gamma-aminopropyltriethoxysilane.

5. A method for preparing a biodegradable medical stent material, characterized in that: The preparation method of the components of a biodegradable medical stent material according to any one of claims 1 to 4 comprises the following steps: S1. Introducing dopamine groups: dissolving polysuccinate in a water-ethanol mixed solvent, adding dopamine, EDC and NHS, reacting at a temperature of 25-35°C for a reaction time of 4-6 hours to obtain dopamine-modified polysuccinate; S2, surface modification and dispersion of nanoparticles: mixing nano magnesium calcium silicate particles with a silane coupling agent, reacting at 40°C for 1.5-2h and then drying, and then adding the nanoparticles to the matrix material obtained in step S1 by ultrasonic dispersion technology; S3, scaffold molding: the above materials are mixed with ammonium bicarbonate in proportion, the mixing temperature is 50-60°C, and then the mixture is placed in a mold and heated to 80-100°C to form a porous structure scaffold; S4. Surface functionalization: The scaffold was immersed in an activation solution containing RGD peptide for 2-4 h, washed and dried to complete the surface modification.

6. The method for preparing a biodegradable medical stent material according to claim 5, characterized in that: The particle size range of the nano magnesium calcium silicate particles in step S2 is 20-50 nm, and the amount of the silane coupling agent used in step S2 is 15-25% of the total weight of the base material.

7. The method for preparing a biodegradable medical stent material according to claim 5, characterized in that: The amount of dopamine groups introduced in step S2 is 3-6% of the total weight of the matrix material.

8. Use of the biodegradable medical scaffold material according to any one of claims 1 to 7 in bone tissue repair, characterized in that: The scaffold material is used to fill bone defects or fracture sites, promotes bone tissue regeneration through its biocompatibility and osteoconductive properties, and gradually degrades within 4-8 weeks.